2022
DOI: 10.23960/jtep-l.v11i1.130-145
|View full text |Cite
|
Sign up to set email alerts
|

Drip Irrigation Technology Performance on Rice Cultivation

Abstract: This study aims to determine the performance of drip irrigation technology as compared to conventional farmer’s practice on rice growth and yield, grain quality, and water consumption. The research was carried out at the Sukamandi Experimental Station, Subang, West Java in July - October 2019. The test was arranged by a nested randomized block design with 5 replications. The main plot was water management with 2 levels: (1) Drip Irrigation Technology (DIT) and (2) Conventional Farmer’s Practice (CFP) (flooded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Results achieved in this study with DRIP and SDI techniques are discussed in the next section. WP Irr increased from 41-108% Sasmita et al (2022). found that drip irrigation reduced by 100% the irrigation water applied and by 6% the grain yield Arbat et al (2018).…”
mentioning
confidence: 90%
“…Results achieved in this study with DRIP and SDI techniques are discussed in the next section. WP Irr increased from 41-108% Sasmita et al (2022). found that drip irrigation reduced by 100% the irrigation water applied and by 6% the grain yield Arbat et al (2018).…”
mentioning
confidence: 90%